AN OVERVIEW ON WELL-BEING THEORIES AND THE ROLE OF INDIVIDUAL RESPONSIBILITY - Morais Campetti, Pedro Henrique de (Revista Ciências Humanas, 2021)
This paper aims to make a theoretical review on the main approaches to Well-being and also introduce the subject of Responsibility as an element to be considered in this discussion. Thus, three theories of well-being are presented: the Mainstream Economics, the Happiness Economics and The Capability Approach. Each of them provides considerations about what matters for people’s life and social development. However, none of them contemplates individual responsibility as a relevant component for development. And only The Capability Approach takes account of responsibility, but without furthering the subject. In this sense, the theme of responsibility is defended as having an important role for development and well-being, and could be incorporated by The Capability Approach.